2016
DOI: 10.1186/s12970-016-0132-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Garcinia mangostana (mangosteen) supplementation does not alleviate physical fatigue during exercise: a randomized, double-blind, placebo-controlled, crossover trial

Abstract: BackgroundThe purple mangosteen (Garcinia mangostana), known as the "queen of fruit," is widely consumed and unique not only because of its outstanding appearance and flavor but also its remarkable and diverse pharmacological effects. The aim of the present study is to evaluate the effect of acute mangosteen supplementation on physical fatigue during exercise.MethodsA randomized, double-blind, placebo-controlled, crossover study was carried out by 12 healthy adults. The participants were randomly assigned to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Although there are no clinical data directly focusing on the effects of MP agents in the depressive patients, several studies have evaluated their impacts on mental health outcomes in humans. In a small randomized controlled trial (RCT), mangosteen-based supplementation containing 305 mg of α-MG and 278 mg of hydroxycitric acid was orally administered to healthy adults prior to cycle ergometer exercise and the parameters directly reflecting the condition of physical fatigue were measured [ 99 ]. All parameters measured showed no differences between the supplementation group and placebo group, except the Profile of Mood States (POMS) scores.…”
Section: Pharmacological Effects Of Mp-derived Agents In Depressiomentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are no clinical data directly focusing on the effects of MP agents in the depressive patients, several studies have evaluated their impacts on mental health outcomes in humans. In a small randomized controlled trial (RCT), mangosteen-based supplementation containing 305 mg of α-MG and 278 mg of hydroxycitric acid was orally administered to healthy adults prior to cycle ergometer exercise and the parameters directly reflecting the condition of physical fatigue were measured [ 99 ]. All parameters measured showed no differences between the supplementation group and placebo group, except the Profile of Mood States (POMS) scores.…”
Section: Pharmacological Effects Of Mp-derived Agents In Depressiomentioning
confidence: 99%
“…All parameters measured showed no differences between the supplementation group and placebo group, except the Profile of Mood States (POMS) scores. The single dose of mangosteen supplementation showed a positive impact on the scores of POMS, a psychological rating scale used to assess transient, distinct mood states [ 99 ].…”
Section: Pharmacological Effects Of Mp-derived Agents In Depressiomentioning
confidence: 99%
“…Due to the association between ROS and fatigue during exercise, Chang et al (109) trialed mangosteen in 12 healthy adults. Participants were randomized to receive an acute dose of either a mangosteen juice blend or a diluted drink that replaced 50% mangosteen juice with water.…”
Section: Clinical Trials Of Mangosteen Pericarpmentioning
confidence: 99%
“…Serum levels of AST, ALT, and plasma ammonia are sensitive biomarkers that reflect the occurrence of physical fatigue. The concentrations of these biomarkers would increase during or after an exercise challenge [ 66 ]. However, although previous studies have shown that treatment with both AM and AS reduced ammonia production in mice in a dose-dependent manner [ 25 , 26 ], such findings were not in accordance with this study.…”
Section: Discussionmentioning
confidence: 99%